Pagamento por serviços ambientais em área de mananciais : estudo de caso do Ribeirão Balainho, São Paulo - Claudete Bezerra dos Santos Canada; Carlos Alberto Mariotoni; Paulo Sergio Franco Barbosa (Confins)
Water demand and water resources availability, along with watershed degradation, must be considered as one of the main threats to the sustainability of São Paulo metropolitan region (RMSP). The urbanization moves toward these spaces, destroying their conditions to produce clean and safe water, being necessary to create actions that guarantee the conservation of upper watershed areas which still are in good conditions. This work aims to propose the implementation of Payments for Environmental Services (PES), coupled with the charges for water use, to be applied to farmers in the Balainho watershed region that includes a spring watershed protection area. For this purpose, a case study and an exploratory visit was carried out. The PES represents a novel instrument capable of providing the necessary stability for farmers exercising their multifunctional role in watersheds.